Study of fertility, fetal survival and prolificacy in relation to social rank in multiparous Iberian sows - Hernández-García F.I.; Bazán J.; Ayuso D.; Izquierdo M.; Corral J.M.; Pérez M.A. (7th International Symposium on the Mediterranean Pig, 2012)
The causes of the low prolificacy of the Iberian pig are unknown, and embryo mortality has not been characterized in this breed, for which breeding and gestation are usually managed in groups, thus resulting in stress related to social hierarchy that could affect its reproductive efficiency. Therefore, the objective of this study was to determine the influence of social rank on fertility, embryo mortality and prolificacy in the Iberian pig. Multiparous Iberian sows (n=39) were weaned at 35±3 postpartum days and then were bred in 4 corrals using 4 boars during ≈40 days. Social rank of sows (R1=dominant; R2=intermediate; R3=subordinate) was determined during feeding, using the 4 corrals up to ≈90 days post-weaning and then a single, larger corral. Sows were scanned by ultrasonography at 20-30, 35-45 and 50-60 post-coitum days. Body weight was similar among ranks. Conception rate at first estrus was lower for R3. Fetal survival after 40 days of gestation was greater for R2 than for R1 and R3. However, R3 sows tended to farrow more live piglets and to yield heavier piglets at weaning.
7. International Symposium on the Mediterranean Pig, 2010/10/14-16, Córdoba (Spain)